American federal systems and COVID-19 : responses to a complex intergovernmental problem - Peters, B. Guy; Grin, Eduardo; Abrucio, Fernando Luiz (Emerald Publishing Limited, 2021)
The COVID-19 pandemic struck as a global problem, a virus spreading without respect for territorial boundaries. National responses to mitigate the multi-dimensional effects provoked by the pandemic have been varied. What factors within federal systems could be related to the success or failure of their attempts to face this crisis? How have political leaders been performing in the intergovernmental arena, along with subnational levels of government? American Federal Systems and COVID-19 analyzes five American federations - Argentina, Brazil, Canada, Mexico, and United States - and how they have responded to a complex intergovernmental problem (CIP) such as the COVID-19 pandemic. Using an analytical model based on two dimensions - institutional design and political agency - this study shows how the combination between federal design and political leadership stances can develop different policy responses to face the challenge of the COVID-19. American Federal Systems and COVID-19 expands the current theoretical and empirical lens and learn what effective and ineffective actions implemented, giving essential insight to face boundary-spanning intergovernmental complex problems whose effects are very unlikely to cease anytime soon.